2022
DOI: 10.48160/25913530di17.204
|View full text |Cite
|
Sign up to set email alerts
|

Desastres rápidos y lentos, y la generación de Enfermedades Transmitidas por Alimentos (ETA) y zoonosis en el antropoceno

Abstract: Este artículo propone realizar un abordaje en torno a los problemas ambientales y desastres naturales, y cómo influyen en la aparición de enfermedades transmitidas por alimentos (ETA) y zoonosis, desde el enfoque de una salud. Para ello, se indaga en las problemáticas de las inundaciones con el caso de Quilmes (2001), la destrucción de humedales y otro desastre como el terremoto y tsunami de Chile (2010). Estos ejemplos, considerados desastres rápidos y lentos, tienen una gran influencia en la inocuidad alimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…In 2004, López reported that 67% of biting dogs evaluated at a rabies health center in Lima had antibody levels > 0.5 IU/mL. 44 Our results may differ from this 2004 study because the sampling schemes and source populations were unique. Specifically, differences included year of analysis, origin of dogs within the city, and differences in laboratory techniques.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In 2004, López reported that 67% of biting dogs evaluated at a rabies health center in Lima had antibody levels > 0.5 IU/mL. 44 Our results may differ from this 2004 study because the sampling schemes and source populations were unique. Specifically, differences included year of analysis, origin of dogs within the city, and differences in laboratory techniques.…”
Section: Discussioncontrasting
confidence: 72%
“…Our results do not show an improvement in the titer of neutralizing antibodies compared with previous studies that reported insufficient population immunity. 44 Also, the lack of detected cases could be due to suboptimal number of brain samples submitted for surveillance from some areas of Lima that do not reach the required canine vaccination coverage. 2 , 33 , 56 Therefore, vaccination strategies must be reevaluated to replicate the high coverage levels achieved in the 1990 s, adapting to the current context.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, es fundamental su abordaje desde las ciencias sociales, incluyendo la mirada jurídica . A su vez, el tratamiento de estos temas de relevancia socio-jurídica genera en el estudiantado aptitudes para relacionarlos con otros campos disciplinares e incrementar su interés en la ciencia y la tecnología (Lampert et. al., 2021).…”
unclassified